TEKNIK ADAPTIF KELOMPOK MUSIK OPSI TOP FOURTY TERHADAP RUANG PERTUNJUKAN DI SURAKARTA - Fariz Hananto (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2019)
ABSTRACTÂ This article aims to reveal and explain adaptive techniques from the Top Fourty OPSI music group in the performance space in the city of Surakarta. This study used two theories, namely the theory of adaptation proposed by Suparlan and Gerungan, as well as the theory and concept of the performance space proposed by Alexander et al. in 1977. Then, the authors also conduct research by participant observation and qualitatively to obtain data in accordance with the facts in the field. From the results of this study, three adaptive techniques were found that need to be done by top fourty musicians, namely (1) the selection of songs, (2) arrangement, and (3) stage expression. The adaptive technique must be truly owned by every top fourty musician, so that they can master any kind of show space to entertain the audience.Â Kata Kunci : musisi top fourty, teknik adaptif, ruang pertunjukan